Cortical representation of species-specific vocalizations in Guinea pig - Suta, Daniel; Popelář, Jiří; Burianová, Jana; Syka, Josef (PLoS One, 2013)
We investigated the representation of four typical guinea pig vocalizations in the auditory cortex (AI) in anesthetized guinea pigs with the aim to compare cortical data to the data already published for identical calls in subcortical structures - the inferior colliculus (IC) and medial geniculate body (MGB). Like the subcortical neurons also cortical neurons typically responded to many calls with a time-locked response to one or more temporal elements of the calls. The neuronal response patterns in the AI correlated well with the sound temporal envelope of chirp (an isolated short phrase), but correlated less well in the case of chutter and whistle (longer calls) or purr (a call with a fast repetition rate of phrases). Neuronal rate vs. characteristic frequency profiles provided only a coarse representation of the calls' frequency spectra. A comparison between the activity in the AI and those of subcortical structures showed a different transformation of the neuronal response patterns from the IC to the AI for individual calls: i) while the temporal representation of chirp remained unchanged, the representations of whistle and chutter were transformed at the thalamic level and the response to purr at the cortical level; ii) for the wideband calls (whistle, chirp) the rate representation of the call spectra was preserved in the AI and MGB at the level present in the IC, while in the case of low-frequency calls (chutter, purr), the representation was less precise in the AI and MGB than in the IC; iii) the difference in the response strength to natural and time-reversed whistle was found to be smaller in the AI than in the IC or MGB.
Keywords: Vocalization, Animal; vokalizace zvířat; Female; sluchové evokované potenciály; Guinea Pigs; morčata; neurony; druhová specificita; Animals; Evoked Potentials, Auditory; sluchové korové centrum; Neurons; akustická stimulace; ženské pohlaví; Acoustic Stimulation; zvířata; Auditory Cortex; Species Specificity